2000
DOI: 10.1046/j.1365-2958.2000.01837.x
|View full text |Cite
|
Sign up to set email alerts
|

A monomeric histidine kinase derived from EnvZ, an Escherichia coli osmosensor

Abstract: SummaryHistidine kinases function as dimers. The kinase domain of the osmosensing histidine kinase EnvZ of Escherichia coli consists of two domains: domain A (67 residues) responsible for histidine phosphotransfer and dimerization, and domain B (161 residues) responsible for the catalytic and ATP-binding function. The individual structures of these two domains have been recently solved by NMR spectroscopy. Here, we demonstrate that an enzymatically functional monomeric histidine kinase can be constructed by fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 27 publications
2
38
0
Order By: Relevance
“…GAF, as well as the DHp subdomain of HPK, may also contribute to CikA dimerization as do the GAF domains of an adenylyl cyclase whose structure has been solved (Qin et al, 2000;Martinez et al, 2005). Thus, the lack of complementation of TH-CikA∆G, and loss of kinase activity, may result from loss of dimerization activity, as natural HPKs are not known to function as monomers (Qin et al, 2000).…”
Section: Model For Function Of Cikamentioning
confidence: 99%
See 1 more Smart Citation
“…GAF, as well as the DHp subdomain of HPK, may also contribute to CikA dimerization as do the GAF domains of an adenylyl cyclase whose structure has been solved (Qin et al, 2000;Martinez et al, 2005). Thus, the lack of complementation of TH-CikA∆G, and loss of kinase activity, may result from loss of dimerization activity, as natural HPKs are not known to function as monomers (Qin et al, 2000).…”
Section: Model For Function Of Cikamentioning
confidence: 99%
“…Thus, the lack of complementation of TH-CikA∆G, and loss of kinase activity, may result from loss of dimerization activity, as natural HPKs are not known to function as monomers (Qin et al, 2000). Alternatively, the importance of GAF may lie with its binding of an unidentified ligand and regulatory aspects associated with bound and unbound changes in conformation of the protein, or through physical interaction with protein partners of its own.…”
Section: Model For Function Of Cikamentioning
confidence: 99%
“…GST fusion proteins and control samples (0.5-5 l) were analyzed on hydrophobic (H4) chips, whereas WhiB3 (his) was analyzed on immobilized metal affinity capture (IMAC-3) chips. In vitro interaction between GST-RpoV and immobilized WhiB3 (his) was performed essentially as described (22) except that PBS with 0.2% Triton X-100 was used as incubation buffer. A saturated solution of ␣-cyano-4-hydroxycinnamic acid in 50% acetonitrile and 0.5% trifluoroacetic acid or ferulic acid in 50% isopropanol and 0.5% trifluoroacetic was used as matrix.…”
Section: Seldi-tofmentioning
confidence: 99%
“…(lanes [25][26][27][28] with all the other experiments], the reason for which is not known at present.…”
Section: Resultsmentioning
confidence: 85%
“…The association of OmpR and EnvZc has been observed by the Ni-nitrilotriacetic acid resin-binding method, either by using His-tagged EnvZc (H. Park & M.I., unpublished data) or His-tagged OmpR (25). Recently, we found that native PAGE is another approach to detecting the interaction between OmpR and EnvZc.…”
Section: Resultsmentioning
confidence: 99%